State Redress and Memory Politics - Arvidsson, Malin; Andersen, Astrid Nonbo (Memory Studies in the Nordic Countries : A Handbook, 2025)
This chapter provides an overview of how claims for state redress have been articulated by memory activists and handled by representatives of the Nordic states from the 1990s to the 2020s. The main types of historical injustices under scrutiny in these processes of “politics of regret” are enslavement and overseas colonialism, abuse in care settings, and forced assimilation of the Sámi and national minorities. The study shows that calls for public apologies, economic compensation, and truth and reconciliation commissions are rarely immediately successful. Over time, however, commemorative activities raising awareness of the rights violations in question as well as public pressure from victims/descendants of victims can result in state apologies, redress schemes, and other forms of reparations. The campaigns analyzed here have been carried out at multiple scales and in relation to several different regions of memory, and comparisons with neighboring countries were often used rhetorically in the political debate.